2010
DOI: 10.1007/s10295-010-0734-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of a recombinant bacterial laccase at low temperature and microaerobic conditions: purification and biochemical characterization

Abstract: Laccases (benzenediol oxygen oxidoreductase; EC 1.10.3.2) have many biotechnological applications because of their oxidation ability towards a wide range of phenolic compounds. Within recent years, researchers have been highly interested in the identification and characterization of laccases from bacterial sources. In this study, we have isolated and cloned a gene encoding laccase (CotA) from Bacillus sp. HR03 and then expressed it under microaerobic conditions and decreased temperature in order to obtain high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 36 publications
5
57
0
3
Order By: Relevance
“…HR03 has been determined [14]. Niladevi et al [24] have found that an unusual halotolerant-alkaline laccase from Streptomyces psammoticus has a molecular mass of about 43 kDa and recently Mohammadian et al [25] determined a molecular weight of 65 kDa for a laccase from Bacillus sp. HR03.…”
Section: Discussionmentioning
confidence: 99%
“…HR03 has been determined [14]. Niladevi et al [24] have found that an unusual halotolerant-alkaline laccase from Streptomyces psammoticus has a molecular mass of about 43 kDa and recently Mohammadian et al [25] determined a molecular weight of 65 kDa for a laccase from Bacillus sp. HR03.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the kinetic parameters obtained for six different BODs at their optimum pH (Durand et al 2012a, b;Durao et al 2008;Kataoka et al 2005b;Koschorreck et al 2008;Mohammadian et al 2010). Insight from crystals structures combined with molecular modelling would be desirable, in order to elucidate the obvious differences among BODs in substrate affinities (Table 1).…”
Section: Biochemical Characterizationmentioning
confidence: 97%
“…The conjugated form results from the transformation of the unconjugated bilirubin in the liver by the enzyme hepatic glucuronyl transferase. The detection of unconjugated bilirubin is more specifically used in newborns where the liver is not mature enough to convert the unconjugated bilirubin to conjugated bilirubin resulting in jaundice affecting~60-80 % of newborns (Goldfinch and Maguire 1988;Kirk 2008; Table 1 Comparison between the kinetics parameters of the BOD from B. pumilus (Durand et al 2012b), B. licheniformis (Koschorreck et al 2008), Bacillus HR03 (Mohammadian et al 2010), B. subtilis (Durao et al 2008), M. verrucaria (Kataoka et al 2005b) and M. oryzae (Durand et al 2012a Mullon et al 1989;Nakamura and Lee 1977). Conjugated bilirubin is known to be a better indicator of liver function and is used in the diagnosis of jaundice and hyperbilirubinemia (Doumas et al 1987(Doumas et al , 1999Kirihigashi et al 2000;Kosaka et al 1987Kosaka et al , 1998Million et al 1988;Mullon and Langer 1987;Perry et al 1986;Soltys et al 1992).…”
Section: Bilirubin and Medical Sensorsmentioning
confidence: 99%
“…The purified laccase showed the lowest K m values (31.2 μ M ) for oxidizing ABTS when compared to the other tested substrates, and the K m value was also significantly lower than other Bacillus strains, which fell in the range of 44-1,404 μ M [Lu et al, 2013;Mohammadian et al, 2010;Sondhi et al, 2014], indicating that the laccase from Bacillus sp. A4 has a much higher affinity for ABTS substrate.…”
Section: Discussionmentioning
confidence: 99%